Percutaneous treatment of a CTO in an anomalous right coronary artery: A rupture paved the way for new insights - Cocco, Nino; Madonna, Rosalinda; Cammalleri, Valeria; Cocco, Giulio; De Stefano, Domenico; Ricciardi, Danilo; Grigioni, Francesco; Ussia, Gian Paolo (Frontiers in Cardiovascular Medicine, 2022)
An anomalous aortic origin of a coronary artery (AAOCA) from the opposite sinus, with an interarterial course, has been associated with an increased risk of myocardial ischemia and sudden death. As the exact pathophysiology of AAOCA is not well understood, the clinical management is also not well defined. With increased use of non-invasive imaging, the diagnosis of AAOCA is increasing and the association of anomalous origin and atherosclerotic disease is becoming a more important topic. We report a rare case of AAOCA chronic total occlusion (CTO). A 40-year-old Caucasian man was referred for invasive coronary angiography (ICA) due to typical chest pain and positive myocardial scintigraphy. ICA demonstrated CTO of an anomalous right coronary artery (ARCA) originating from the left side of the ascending aorta with an interarterial course. There was no lesion in the left coronary artery. During the procedure, unexpected rupture of the coronary artery occurred after dilatation with a small balloon at low pressure. The complication in this case was handled with good procedural final result but was an occasion for a food for thought. Coronary artery perforations are rare but life-threatening procedural complications that are usually caused by predisposing anatomical and procedural factors. We issue a warning on the risk of complications during complex percutaneous coronary intervention of these arteries, and we reconsidered the pathophysiology of the anomaly in a way that could change the approach to the disease. Based on this complication, we hypothesized that the wall of the artery could be fragile due to histopathological alterations, which could have a role in the pathophysiology of coronary malignancy. Future autopsy studies should be focused on the analysis of the arterial wall of the patient affected by sudden death with this anomaly.